Invasive Weed Species in Malaysian Agro-Ecosystems : Species, Impacts and Management - Hj Bakar, Baki (Malaysian Journal of Science, 2004)
Theoretical considerations on the paths of invasion of weeds are described with special mention of the invasive traits and spread of weedy species in terrestrial and aquatic agro-ecosystems in Malaysia. A sizeable number of introduced, naturalized, and native plant species in Malaysia have established and spread as invasive weed species, and some are classified as scheduled pests under the Plant Quarantine Act 1976 and Plant Quarantine Regulations 1981. Population increase, intensive agricultural and forestry practices, urbanization, and degradation and fragmentation of natural habitats are some of the driving anthropogenic and non-anthropogenic forces that increase the movement of weed species and new invasions. Today there are more than 100 weed species in our agro-ecosystems, many of which are invasive. The paths of invasion of weeds in our agro-ecosystems are largely unknown. Management of invasive weed species in Malaysian agro-ecosystems are very much herbicide-based, integrated with other control measures including cultural practices, prescribed burning, animal grazing, and to certain extent, followed by manual and mechanical roughing. Successful management of noxious invasives in our ecosystems will require the development of a long-term strategy incorporating prevention programmes, extension and educational activities, and sustainable and educational multi-year integrated approaches that prevent reinvasion or encroachment by other noxious invasive weed species. Invasive weed species impact on public awareness, legislation, conservation biology, agriculture, forestry, soil and water resources, and recreational and other related activities in the Malaysian agriculture and waterways management. One can easily visualize the extent of measurable economic impact of these invasives by the amount of herbicides sold per year in Malaysia to combat this menace. During 1991-1999, herbicides accounted for RM220-230 millions/year or 76-79% of the total pesticide sales in Malaysia. If the costs of weed management operations yield and quality losses of crops, disease and pest occurrences (weeds being the alternative hosts of many diseases and pests) are taken into account, the figures can be quite monumental. Other social impacts are discussed